7th International Symposium on High-Temperature Metallurgical Processing - Hwang, Jiann-Yang; Jiang, Tao; Pistorius, Chris; Alvear, Gerardo; Yucel, Onuralp; Cai, Liyuan; Zhao, Baojun; Gregurek, Dean; Seshadri, Varadarajan (The Minerals, Metals & Materials Series,, 2016)
The technology, operation, energy, environmental, analysis, and future development of the metallurgical industries utilizing high temperature processes are covered in the book. The innovations on the extraction and production of ferrous and nonferrous metals, alloys, and refractory and ceramic materials, the heating approaches and energy management, and the treatment and utilizations of the wastes and by-products are the topics of special interests. This book focuses on the following issues: •High Efficiency New Metallurgical Process and Technology Fundamental Research of Metallurgical Process •Alloys and Materials Preparation •Direct Reduction and Smelting Reduction •Coking, New Energy and Environment •Utilization of Solid Slag/Wastes and Complex Ores •Characterization of High Temperature Metallurgical Process.